2014
DOI: 10.1089/neu.2013.3000
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Magnetic Resonance Imaging Study of the Apparent Diffusion Coefficient Values in Corpus Callosum during the First Year after Traumatic Brain Injury

Abstract: The objective of this study was to explore the evolution of apparent diffusion coefficient (ADC) values in magnetic resonance imaging (MRI) in normal-appearing tissue of the corpus callosum during the 1st year after traumatic brain injury (TBI), and relate findings to outcome. Fifty-seven patients (mean age 34 [range 11-63] years) with moderate to severe TBI were examined with diffusion weighted MRI at three time points (median 7 days, 3 and 12 months), and a sexand age-matched control group of 47 healthy indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…For more details on regions I-V of the corpus callosum, we refer the reader to the Methods section or Moen and colleagues. 22 No significant differences between the ''all TBI'' patients and the controls ( p = 1.0) were found in any regions (MWU with Bonferroni's correction). No significant differences between the patients with MRI £ 7 days versus 8-28 days postinjury ( p = 0.69-1.0) were found in any regions (MWU with Bonferroni's correction).…”
Section: Mean Apparent Diffusion Coefficient Changes In Normal Appearmentioning
confidence: 87%
See 2 more Smart Citations
“…For more details on regions I-V of the corpus callosum, we refer the reader to the Methods section or Moen and colleagues. 22 No significant differences between the ''all TBI'' patients and the controls ( p = 1.0) were found in any regions (MWU with Bonferroni's correction). No significant differences between the patients with MRI £ 7 days versus 8-28 days postinjury ( p = 0.69-1.0) were found in any regions (MWU with Bonferroni's correction).…”
Section: Mean Apparent Diffusion Coefficient Changes In Normal Appearmentioning
confidence: 87%
“…More details of diffusion MRI acquisition has been described earlier. 22 Counting of lesions in the different magnetic resonance imaging sequences…”
Section: Magnetic Resonance Imaging Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Previous studies suggest that changes of ADC values in the corpus callosum and BS are associated with the outcomes. 23,34,35 We quantitatively tested the water diffusion in the predilection areas of DAI (CS, corpus callosum and BS) and found that the increased ADC values in patients with TBI were comparable to those in the control subjects, which can be explained by the compromised obstruction of the broken axonal membrane, or they may be due to residual oedema. The ADC values in the CCS and BS were significantly increased in patients with unfavourable outcomes, and the ADC ccs proved to be an independent risk factor for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior studies were conducted either on the basis of retrospective, social or statistical methods to ascertain a possible correlation between age, gender and occurrence of brain tumors [11][12][13][14][15][16][17][18]21].…”
Section: Introductionmentioning
confidence: 99%